Pengaruh Kombinasi NPK dan Pupuk Kandang terhadap Sifat Tanah dan Pertumbuhan serta Produksi Tanaman Caisim - . Sarno (UNIVERSITY OF LAMPUNG, 2009)
The study was conducted in Keputran village, Tanggamus District, Lampung Province. The aim of this study to find out a proper combination of NPK fertilizer and chicken manure for the vegetable crops, especially chinese mustard (Brassica campetris Var. Chinensis L.) in order to increase the production. A randomized complete block design was used in this experiment with ten treatments and three replications. The result showed that the application of chicken manure with the dosage of less than 5 Mg ha-1 was combined with NPK fertilizer did not effective to affect the increasing of growth and production of chinese mustard. Meanwhile application of chicken manure more than 5 Mg ha-1 was combined with NPK fertilizer significantly affected the growth, production of chinese mustard and soil properties i.e. C-total, total-N, P available, exchangeable K, and humic and fulvic acid. The application of chicken manure effective to reduce NPK fertilizer need. The best yield was found in using 50% of NPK fertilizer to dosage recommendation and 50% application of chicken manure to dosage 20 Mg ha-1.